CRIMINAL ACTS FOR EVENT ORGANIZERS ONLINE GAME TOURNAMENT ORGANIZERS WHO RECEIVE SPONSORSHIP FROM ONLINE GAMBLING SITES BASED ON INDONESIAN CRIMINAL LAW - Ahmad, Risyad Fadhillah (Faculty of Law Universitas Trunojoyo Madura, 2023)
Gambling is currently rife in the world of internet media, utilizing social media as a means of promoting gambling-laden content. However, in terms of strengthening the law on betting crimes in Indonesia, law enforcement seems to be selective logging. This can be proven by the existence of event organizers who install gambling sponsors, which are then held directly at offline venues. They are also covered and broadcast live on the YouTube platform and in posts on Instagram social media. Even though gambling is a criminal offence, its distribution is included in the criminal acts regulated in Article 27, paragraph (2) of Law No. 11 of 2008 concerning Electronic Information and Transactions. The formulation of the problem in this study is how to place criminal law for event organizers who promote gambling and what sanctions are received if there is a violation. This research is normative legal research with a legal approach.